Electrochemical Studies of LbL Films With Dawson Type Heteropolyanion Glassy Carbon Electrode Sensor Modified for Methyl Parathion Detection - Ditta, Nafeesa Allah; Yaqub, Mustansara; Nadeem, Sohail; Jamil, Sundas; Hassan, Sadaf Ul; Iqbal, Shahid; Javed, Mohsin; Elkaeed, Eslam B.; Alshammari, Fwzah H.; Alwadai, Norah; Alzhrani, Rami M.; Awwad, Nasser S.; et al. (Frontiers in Materials, 2022)
Rapid detection of methyl parathion was measured by using a fabricated glassy carbon electrode (GCE) sensor which was designed by the layer by layer (LBL) method. Multilayers assemblies were developed on the glassy carbon electrode by alternating depositions of anions and cations in which a Dawson Type Polyoxometalate β-K6[(P2W18O62·H2O)]·14H2O (~ P2W18 POM)} and polyethyleneimine (PEI) stabilized silver nanoparticles (~ PEI-AgNPs) were acted as anions and cations respectively. The redox behavior of P2W18 POM within LBL assembly was carried out via cyclic voltammetry. This LBL assembly was thoroughly characterized by UV-Visible, FT-IR, XRD, AFM, and SEM techniques. The fabricate GCE sensor was investigated for the electrocatalytic activity for the detection of methyl parathion. The results clearly showed that the fabricated GCE sensor was successfully synthesized and more interestingly the current response for the detection of methyl parathion was found at less than 1 ppm which proved that this fabricated GCE sensor may exhibit potential applications in the detection of targeted pesticide.